Improving teacher competence in supporting students with special needs through psychoeducation - Rahmi, Iftita; Damra, Hanny Rufaidah; Rozi, Muhamad Fahrur; Dalimunthe, Hanifa Laura (Universitas Muhammadiyah Magelang, 2025)
Inclusive education in Indonesia continues to face significant challenges, particularly concerning infrastructure and human resources. A key obstacle is the lack of teacher competence in understanding the needs of students with special educational needs (SENs) and developing individualized education programs (IEPs). This deficit hinders the effective implementation of inclusive education in regular schools. The purpose of this community service was to enhance the knowledge and skills of teachers through a psychoeducation and IEP development training program at SDN 04 IX Korong, Solok City. The program consisted of two main activities: first, psychoeducation sessions on the characteristics, identification, and intervention strategies for students with special educational needs; and second, hands-on training to enable teachers to develop appropriate IEPs. The program's effectiveness was evaluated using the Kirkpatrick model, focusing on the reaction and learning levels. The results demonstrated a significant improvement in teacher competence. Post-test scores showed a 90% increase in participants' understanding and ability to identify and intervene with students with SENs. A paired-sample t-test confirmed a statistically significant difference between pre-test and post-test scores (p < 0.005), indicating that the training successfully equipped teachers to manage diverse student needs and foster a more inclusive learning environment. The findings underscore the importance of continuous professional development for teachers to support higher-quality inclusive education at the elementary level, especially in schools lacking dedicated staff for students with special needs.